Patient and Family Engagement: The Secret Behind Quality Healthcare Services (Literature Review) - Ahyar Wahyudi; Iwan Trihapsoro; Listyo Yuwanto; Ratna Indrawati; Hisnindarsyah; Buyung Nazeli (PT FORMOSA CENDEKIA GLOBAL, 2023)
World Patient Safety Day 2023 underscores the significance of patient engagement, aligning with the principles advocated by Don Berwick. This article underscores the importance of involving patients and their families in healthcare services, with a focus on effective communication, cultural differences, varied levels of patient engagement, access to information, privacy, and resource constraints. The concept of